Effect of Pb-acetate on Testicle Weight and Volume of Mice - Isradji, Israhnanto (Sains Medika : Jurnal Kedokteran dan Kesehatan, 2011)
Background: The human effort to meet the needs of human life is almost always cause pollution in the environment of his life. One of the pollutants that harm human beings are lead (Pb = plumbum), Pb is one of the heavy metals that are harmful to health. Pb may also affect the reproductive organs. The purpose of this study to determine the effect of Pb-acetate on mouse testis weight and volumeDesign and Method: Eighty male mice placed in individual cages according to the group. Food and drink provided ad libitum. The treatment of male mice given for 6 weeks. Treatment with 0.2 ml distilled water to PI, P II were given a solution of 400 ppm Pb acetate total of 0.2 ml, P III was given a solution of 1000 ppm Pb acetate as many as 0.2 ml, and P IV were given a solution of 2000 ppm Pb acetate total of 0,2 ml by using a gastric sonde, every morning once a day for 42 days. At week 7, mice were surgery to take the testis. Testicular volume was measured and weighed. Data were analyzed by ANOVA, hypothesis is accepted when p<0.05, to know the difference between the effect of treatment used the least smallest difference test.Result: The weight of the testes treated with Pb-acetate 0 ppm, 400 ppm 1000 ppm and 2000 ppm consecutive is 0.237, 0.237, 0.227 and 0.217 g, Volume testes treated with Pb acetate concentrations of 0 ppm, 400 ppm 1000 ppm and 2000 ppm consecutive is 0.278, 0.273, 0.255 and 0.263 cm3, respectively testicular volume Anova test results obtained by the probability of 0.189 (> 0.05), testis weight obtained by ANOVA test probability of 0.216 (> 0.05), mean Pb -acetate had no effect on testis weight and volume.Conclusion: Pb-acetate had no effect on testis weight and volume (Sains Medika, 3(2):150-156).